Critical Discourse Analysis Ruth Wodak in The “ Bocah-Bocah Kosong” Youtube Video - Hetty Mery Marbun; Elly Manika Maya Mahadi; Gesilva Putri Samya Shaabiriina; Pramudya Ardhika Hernanto (Dinasti International Journal of Education Management And Social Science, 2025)
The entertainment industry is experiencing a notable evolution in humor, exemplified by the widely acclaimed content “Bocah-Bocah Kosong” on the YouTube WKWK Project by Genflix, which features women characterized by their oriental appearances and "Kosong" personas. This study seeks to elucidate the exploitation and manipulation prevalent within the entertainment industry through the application of Ruth Wodak's critical discourse analysis framework. The investigation was conducted by analyzing the textual content of episodes 1 to 30 of “Bocah-Bocah Kosong,” supplemented by interviews with four members of the production team, observational methods, and a review of relevant literature. The findings of this study, within the framework of cognitive dimension analysis, indicate that the production team engaged in exploitation throughout the entire process, from planning to scripting. The examination of the socio-psychological dimensions reveals that the manipulation of innocence, ignorance, and sexuality is employed to construct the identities of the characters in “Bocah-Bocah Kosong” through diverse modes of communication. An analysis of the linguistic dimension revealed that manipulative disclaimers were employed to evoke humor and exploit themes of innocence, ignorance, and sexuality as overarching narratives, alongside the strategic use of editing to enhance the text's impact. This manipulation is normalized by the entertainment business, which is ironic given that the owner of Genflix is a woman.